The Potential Role of Qard Hasan Based Baitul Maal Wa Tamwil in Realizing Financial Inclusion - Rohman, Pupun Saepul; Fianto, Bayu Arie; Laila, Nisful; Ascarya, Ascarya (AMWALUNA (Jurnal Ekonomi dan Keuangan Syariah), 2023)
This study aims to describe the potential role of the qard hasan-based Baitul Maal wa Tamwil (BMT) in achieving financial inclusion. This article uses a literature study approach accompanied by a case study. This study concludes that financial inclusion in society is very likely to be realized by the practice of the qard hasan contract at BMT. The implications of this research can be useful for policy makers related to BMT and Islamic microfinance more broadly. This can help policy makers and regulators understand the challenges and opportunities in supporting and promoting financial inclusion through BMTs.